Two minor determinants of myelin basic protein induce experimental allergic encephalomyelitis in SJL/J mice (The Rockefeller University Press, 1988)
Experimental allergic encephalomyelitis (EAE) is an autoimmune demyelinating disease of the central nervous system (CNS) that occurs after immunization of animals with myelin basic protein (MBP). The disease is a prototype model for the study of antigen-specific T helper cell-mediated autoimmune disease. In SJL/J mice, EAE is mediated by T helper cells directed against a 40-amino acid COOH-terminal peptic fragment of mouse small MBP. To identify the minimal T cell epitopes of MBP responsible for EAE, overlapping peptides completely encompassing the epitopes within this region were synthesized. A 28-residue peptide of mouse MBP spanning residues 87-114 (pM87-114) was able to elicit both a strong T cell response and chronic relapsing disease. To better localize the T cell epitopes, shorter peptides within this region were synthesized and two overlapping peptides, pM87-98 and pM91-104, were able to induce EAE. T cell clones and bulk lymph node cell populations reactive with pM87-98 did not respond to pM91-104. However, lymph node cells reactive with pM91-104 also reacted with pM87-98, thus showing that these two peptides represent contiguous, but distinct encephalitogenic epitopes and that both these epitopes may be contained within pM87-98. In addition, pM87-114 and pM87-98 were found to be minor determinants of the total T cell response to rat and rabbit MBP. The restricted response to MBP in SJL/J mice is similar to that of the PL/J mice in that each appears to have only a single peptide region in MBP that elicits encephalitogenic T cells. However, within the region studied, there were two if not more T cell epitopes. This differs from the single encephalitogenic PL/J epitope. These findings of a single encephalitogenic peptide region with multiple T cell epitopes and the fact that encephalitogenic T cell epitopes may be subdominant have implications for the design of treatments directed at the T cell receptor-MHC-peptide epitope complex in autoimmune disease.